Synthesis of collagen from Bali cattle's hide using a combination of acid and alkali on the extracting process - Said, M. I.; Burhan, B.; Tensi, T.; Haerati, H. (Diponegoro University, 2018)
The process of pre-extraction is an important stage in the process of collagen synthesis. This stage increases the sensitivity of collagen molecule chains that can affect production yields and collagen properties. The objectives of the study were to synthesize and evaluate halal collagen from Bali cattle’s hide on different -extracting processes. A total of 5 treatments applied in this study, namely: T1 = Ca(OH)2 5% (b/v) ; T2= Ca(OH)2 15% (b/v) ; T3= Ca(OH)2 5% + CH3COOH 5%(b/v) ; T4= Ca(OH)2 15% + CH3COOH 5% (b/v). Each treatment was repeated 4 times. Data were analyzed in a variety of ways using SPSS program. The observed parameters consisted of: 1) yield, 2) viscosity and 3) pH. The results showed that the difference in real pre-extracting process increased the yield and viscosity, but not the pH value. The application of T4 treatment provided the best results compared to other treatments as well as controls to increase the yield and also improve the collagen's physical properties and pH.